Farmers' manual on small-scale tilapia pond farming in Ghana - Agyakwah, Seth K.; Asmah, Ruby; Mensah, Emmanuel Tetteh-Doku; Ragasa, Catherine; Amewu, Sena; Tran, Nhuong; Oyih, Mathew; Ziddah, Peter (Water Research Institute, 2020)
This manual provides a comprehensive step-by-step guide to pond aquaculture. It includes tips on site selection, site preparation, pond design and construction, farming practices (pond preparation, stocking, and feeding), biosecurity and fish health management, harvesting and marketing and recordkeeping - all of which are critical elements of a successful tilapia pond aqua-farming business operation. Aquaculture has existed in Ghana since the 1950s, though the sector didn’t experience major growth until around 2000, when large-scale commercial production began. Today, it plays a key role in the nation’s prosperity, contributing to food security by augmenting domestic fish production and creating jobs. Even so, challenges that have historically plagued the sector and hindered growth remain pervasive. These include low technical know-how and a lack of quality inputs such as seed and feed. Although knowledge in the sector has increased over the years, small-scale farmers (most of whom are indigenous) continue to struggle with basic farming practices. As a result, they’re often faced with poor yields, which can ultimately lead to a farm’s collapse. The Tilapia Seed Project is aimed at accelerating quality tilapia seed production and dissemination in Ghana. Project stakeholders produced this manual to provide accurate direction to small-scale fish farmers in Ghana. After reviewing its contents, we expect that it will prove instrumental in helping farmers improve production, and that it will serve as a valuable catalyst for growth in this important sector.